Interplay Among the Oral Microbiome, Oral Cavity Conditions, the Host Immune Response, Diabetes Mellitus, and Its Associated-Risk Factors-An Overview - Thais de Cássia Negrini; Iracilda Zeppone Carlos; Cristiane Duque; Karina Sampaio Caiaffa; Rodrigo Alex Arthur (Frontiers Media S.A., 2021)
This comprehensive review of the literature aimed to investigate the interplay between the oral microbiome, oral cavity conditions, and host immune response in Diabetes mellitus (DM). Moreover, this review also aimed to investigate how DM related risk factors, such as advanced age, hyperglycemia, hyperlipidemia, obesity, hypertension and polycystic ovary syndrome (PCOS), act in promoting or modifying specific mechanisms that could potentially perpetuate both altered systemic and oral conditions. We found that poorly controlled glycemic index may exert a negative effect on the immune system of affected individuals, leading to a deficient immune response or to an exacerbation of the inflammatory response exacerbating DM-related complications. Hyperglycemia induces alterations in the oral microbiome since poor glycemic control is associated with increased levels and frequencies of periodontal pathogens in the subgingival biofilm of individuals with DM. A bidirectional relationship between periodontal diseases and DM has been suggested: DM patients may have an exaggerated inflammatory response, poor repair and bone resorption that aggravates periodontal disease whereas the increased levels of systemic pro-inflammatory mediators found in individuals affected with periodontal disease exacerbates insulin resistance. SARS-CoV-2 infection may represent an aggravating factor for individuals with DM. Individuals with DM tend to have low salivary flow and a high prevalence of xerostomia, but the association between prevalence/experience of dental caries and DM is still unclear. DM has also been associated to the development of lesions in the oral mucosa, especially potentially malignant ones and those associated with fungal infections. Obesity plays an important role in the induction and progression of DM. Co-affected obese and DM individuals tend to present worse oral health conditions. A decrease in HDL and, an increase in triglycerides bloodstream levels seem to be associated with an increase on the load of periodontopathogens on oral cavity. Moreover, DM may increase the likelihood of halitosis. Prevalence of impaired taste perception and impaired smell recognition tend to be greater in DM patients. An important interplay among oral cavity microbiome, DM, obesity and hypertension has been proposed as the reduction of nitrate into nitrite, in addition to contribute to lowering of blood pressure, reduces oxidative stress and increases insulin secretion, being these effects desirable for the control of obesity and DM. Women with PCOS tend to present a distinct oral microbial composition and an elevated systemic response to selective members of this microbial community, but the association between oral microbiome, PCOS are DM is still unknown. The results of the studies presented in this review suggest the interplay among the oral microbiome, oral cavity conditions, host immune response and DM and some of the DM associated risk factors exist. DM individuals need to be encouraged and motivated for an adequate oral health care. In addition, these results show the importance of adopting multidisciplinary management of DM and of strengthening physicians-dentists relationship focusing on both systemic and on oral cavity conditions of DM patients.